Comparison of the Parkes and FAST FRB DM distribution. Issue 2 (11th March 2022) - Arcus, W R; James, C W; Ekers, R D; Wayth, R B
ABSTRACT: We model the fast radio burst (FRB) dispersion measure (DM) distribution for the Five-hundred-meter Aperture Spherical Telescope (FAST) and compare this with the four FRBs published in the literature to date. We compare the DM distribution of Parkes and FAST, taking advantage of the similarity between their multibeam receivers. Notwithstanding the limited sample size, we observe a paucity of events at low DM for all evolutionary models considered, resulting in a sharp rise in the observed cumulative distribution function in the region of 1000 pc cm −3 ≲ DM ≲ 2000 pc cm −3 . These traits could be due to statistical fluctuations (0.12 ≤ p ≤ 0.22), a complicated energy distribution or break in an energy distribution power law, spatial clustering, observational bias, or outliers in the sample (e.g. an excessive DMHost as recently found for FRB 20190520B). The energy distribution in this regime is unlikely to be adequately constrained until further events are detected. Modelling suggests that FAST may be well placed to discriminate between redshift evolutionary models and to probe the helium ionization signal of the intergalactic medium.